Proceedings of the 2016 ACM SIGPLAN International Conference on Generative Programming: Concepts and Experiences 2016
DOI: 10.1145/2993236.2993256
|View full text |Cite
|
Sign up to set email alerts
|

Automatic non-functional testing of code generators families

Abstract: The intensive use of generative programming techniques provides an elegant engineering solution to deal with the heterogeneity of platforms and technological stacks. The use of domain-specific languages for example, leads to the creation of numerous code generators that automatically translate highlevel system specifications into multi-target executable code. Producing correct and efficient code generator is complex and error-prone. Although software designers provide generally high-level test suites to verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In fact, execution times were at least 40 times longer than for morphs targeting other languages. Checking results with authors from previous work [16], [17], they also have noticed this anomaly and reported it to Haxe community in a bug report. Developers responded that they knew about it, it was fixed already but the patch was not live when [16], [17] conducted their study.…”
Section: (Haxe Case) Can We Discover Bugs Thanks To the Dispersion Scsupporting
confidence: 63%
See 4 more Smart Citations
“…In fact, execution times were at least 40 times longer than for morphs targeting other languages. Checking results with authors from previous work [16], [17], they also have noticed this anomaly and reported it to Haxe community in a bug report. Developers responded that they knew about it, it was fixed already but the patch was not live when [16], [17] conducted their study.…”
Section: (Haxe Case) Can We Discover Bugs Thanks To the Dispersion Scsupporting
confidence: 63%
“…Morphs. Based on previous works presented in [16], [17], we selected 4 popular target languages namely C++, C#, Java, PHP. Then, we tuned code generators according to several optimization parameters they provide.…”
Section: Haxe Case (Code Generator)mentioning
confidence: 99%
See 3 more Smart Citations